Analgesia obstétrica farmacológica: um estudo sobre os desfechos obstétricos e neonatais - Ruanna Lorna Vieira Fernandes; Ana Kelve de Castro Damasceno; Marta Maria Soares Herculano; Raquel de Serpa Torres Martins; Mônica Oliveira Batista Oriá (Universidade Federal do Ceará, 2017)
Objective: to investigate the association between pharmacological obstetric analgesia and obstetric and neonatal outcomes. Methods: it was a retrospective case-control study conducted with 393 pregnant women comprising 131 cases of pharmacological obstetric analgesia and 262 controls that did not perform this procedure. The sociodemographic and obstetric profile, the circumstances of parturient admission, obstetrical decisions, and obstetric and neonatal outcomes were investigated. Results: pregnant women submitted to pharmacological analgesia during labor presented an increased risk for the use of exogenous oxytocin (p<0.001), episiotomy (p=0.001), Kristeller maneuver (p=0.036), and forceps (p=0.004). Conclusion: pharmacological analgesia does not increase the risk of spontaneous perineal tear, abdominal delivery, and hospitalization in neonatal unit. Nevertheless, it influences the increased risk of synthetic oxytocin use, Kristeller maneuver, episiotomy, forceps, and the occurrence of lower first-minute Apgar scores.